Synthesis and characterization of Ce-substituted hydroxyapatite by sol-gel method - Kaygili, Omer; Dorozhkin, Sergey V.; Keser, Serhat (Elsevier Science Bv, 2014)
Both undoped hydroxyapatite (HAp) and three Ce-substituted HAp samples with variable amounts (from 0.5 to 2 at.%) of Ce were synthesized by sol-gel method. The samples were studied by X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) spectroscopy to determine the crystallite size, crystallinity degree, phases, functional groups, morphology and elemental composition. In all samples, the amount of HAp exceeded 92%, while the amount of admixture beta-TCP was always below 8% and no changes were observed by addition of Ce. The crystallinity degree of the samples was always within 84-89%, while the calculated dimensions of crystallites appeared to be within 26-35 nm. The microstructure and elemental composition of all the samples were found to be affected by the addition of Ce. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Hydroxyapatite; Cerium substitution; Sol-gel method; Bioceramics